Delamination damage analysis of laminated bonded tubular single lap joint made of fiber-reinforced polymer composite. (August 2014) - Das, Rashmi Ranjan; Pradhan, Brajabandhu
Onset and growth of delamination damages in laminated fiber-reinforced polymer composite made bonded tubular single lap joints have been thoroughly studied through a finite element analysis-based simulation technique developed in the present research. The model provides sufficient scope for a comprehensive parametric study of the bonded structure in terms of three-dimensional stress analyses within the joint, studying the delamination damage onset and growth characteristics, and investigating its effect on stress distributions in the joint and both the adherends (outer and inner). Quadratic failure criterion has been used to depict delamination damage-induced cohesion failure within the adhesive layer. Whereas Tsai–Wu coupled stress criterion has been used for locating the delamination and adhesion failure prone regions at ply-interfaces of the adherends and adherend–adhesive interfaces within the joint, respectively. Three-dimensional stress analyses revealed that outer adherend of the bonded tubular single lap joints experiences comparatively higher interlaminar peel (σ r ) and shear stress (τ rz, τ r θ ) concentrations at the free edge of the first ply-interface and is likely to delaminate at this edge. Accordingly, pre-embedded through-the-circumference delamination damages have been simulated at this edge, and contact finite element analyses have been performed in order to avoid interpenetration of delaminated surfaces. Strain energy release rate calculated using modified crack closure integral vis-à-vis virtual crack closure technique has been used as the characterizing parameter for assessing the growth of the damages. Free edge delamination in the outer adherend has been observed to propagate in a self-similar manner mainly in the in-plane shearing mode. It causes peel and shear stress concentrations in regions of the adherend–adhesive interfaces and first ply-interface of the inner adherend, localized to the clamped edge of the joint making the joint and the adherend prone to adhesion failure and delamination damage, respectively.